A stable and porous iridium(iii)-porphyrin metal–organic framework: synthesis, structure and catalysis. Issue 12 (4th March 2016) - Cui, Hao; Wang, Yingxia; Wang, Yanhu; Fan, Yan-Zhong; Zhang, Li; Su, Cheng-Yong
Abstract : A porous iridium(iii )-porphyrin metal–organic framework with high stability has been prepared, which can promote the carbenoid insertion into O–H bonds. Abstract : Self-assembly of a new metalloporphyrin tetracarboxylic ligand Ir(TCPP)Cl (TCPP = tetrakis(4-carboxyphenyl)porphyrin) with ZrCl4 in the presence of benzoic acid leads to the formation of a three-dimensional (3D) iridium(iii )-porphyrin metal–organic framework (Ir-PMOF) with the formula of [(Zr6 (μ3 -O)8 (OH)2 (H2 O)10 )2 (Ir(TCPP)Cl)3 ]·solvents (Ir-PMOF-1 (Zr)), which possesses square-shaped channels of 1.9 × 1.9 nm 2 (atom-to-atom distances across opposite Ir metal atoms) in three orthogonal directions as disclosed by the single-crystal X-ray diffraction analysis. Ir-PMOF-1 (Zr) represents the first MOF bearing a self-supporting iridium-porphyrin catalytic framework, featuring high porosity and stability. The catalytic tests disclose that the activated Ir-PMOF-1 (Zr) can promote O–H insertion with a turnover frequency (TOF) up to 4260 h −1 . Ir-PMOF-1 (Zr) can be recycled and reused for 10 runs without significant loss of catalytic activity, and the total turnover number (TON) for O–H insertion after 10 successive runs reaches 875.